Archéologie participative avec les Wayana dans les Tumuc-Humac (Mont Mitaraka, crique Alama, Guyane Française) - Marie Fleury; Aimawale Opoya; Aitalewa Palanaiwa; Anaima Putpu; Daniel Sabatier; Martijn van den Bel (Revue d'ethnoécologie)
This indigenous archaeological mission in the Mitaraka region, part of the Tumuc Humac Plateau, is the continuation of a previous project led by Marie Fleury concerning the indigenous cartography of ancient Wayana dwellings as well as the naturalistic expedition Planète revisitée, organized by the National Museum of Natural History and the NGO Pronatura. Many archaeological objects were discovered during both missions, suggesting an important ancient human occupation of this particular region. Moreover, the oral history of the Wayana pin-points the genesis of their people in this particular part of the Tumuc Humac Plateau. In October 2018, three researchers and three Wayana went on a mission there and were able to identify eight archaeological sites and three more possible sites with an average of one site per km2. The discussion and comparison of the interpretations of these sites between scientists and Wayana has significantly enriched the historical knowledge of this region. A few radiocarbon dates confirmed that this area has been occupied for at least two thousand years.